Садово-огородный участок: справочное пособие / В. В. Таранов, Е. А. Таранова - Таранов Василий Васильевич (Агропромиздат, 1985)
Экземпляры: (20151001) / Инвентарный номер: 9872 / Сис.шифр: 42.3 / Авт.знак: Т 19 / ББК: 42.3я22